2001
DOI: 10.1002/ejsp.86
|View full text |Cite
|
Sign up to set email alerts
|

Testing the group polarization hypothesis by using logit models

Abstract: This paper focuses on methodological aspects of group polarization research and has two well-de®ned parts. The ®rst part presents a methodological overview of group polarization research together with an examination of the inadequacy, under certain circumstances, of the traditional parametric approach usually used to test this phenomenon based on pre-test/post-test means comparison across groups. It is shown that this approach will produce masks effects when groups are heterogeneous with regard to the observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We conducted an analysis of polarization scores because Rodrigo and Ato ( 50 ) showed that changes in the means on an aggregate level, as in an (M)ANOVA, do not provide unequivocal evidence of the presence or absence of polarization. To assess the extent of polarization, we first determined whether an individual posttest item response showed a shift toward a higher value on the same pole as its pretest counterpart.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted an analysis of polarization scores because Rodrigo and Ato ( 50 ) showed that changes in the means on an aggregate level, as in an (M)ANOVA, do not provide unequivocal evidence of the presence or absence of polarization. To assess the extent of polarization, we first determined whether an individual posttest item response showed a shift toward a higher value on the same pole as its pretest counterpart.…”
Section: Methodsmentioning
confidence: 99%
“…Another type of attitudinal change results from attitude polarization, which is the tendency to shift toward a more extreme position on the same pole of the attitude continuum. This can occur after group discussion ( 39,50 ) or by personal reflection. ( 51 ) Specifically, when group members begin their discussions by having generally similar nonneutral attitudes, any relevant, valid, and novel arguments that are shared during group discussions tend to be consistent with members’ existing attitudes, thus increasing their confidence in the correctness of these attitudes.…”
Section: Introductionmentioning
confidence: 99%